Numerical simulation of dynamic brittle fracture of pipeline steel subjected to DWTT using XFEM-based cohesive segment technique (Fracture and Structural Integrity, 2016)
In the past several numerical studies have addressed the ductile mode of fracture propagation. However, the brittle mode of pipeline failure has not received as much attention yet. The main objective of this study is to predict brittle fracture behaviour of API X70 pipeline steel by means of a numerical approach. To this end, the eXtended Finite Element Method (XFEM)-based cohesive segment technique is used to model Drop Weight Tear Test (DWTT) of X70 pipeline steel at -100°C. In this model the dynamic stress intensity factor and crack velocity are calculated at the crack tip at each step of crack propagation.
Keywords: Dynamic brittle fracture; Pipeline steel; Cohesive segment